2015
DOI: 10.3109/03014460.2015.1071424
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in hair trace elements: a cross-sectional study in Orenburg, Russia

Abstract: Hair Cr, Mn, Ni, Si, Al, As, Be, Cd and Pb tended to decrease with age in the female sample, whereas hair Cu, Fe, I, Se, Li and Sn were characterised by an age-associated increase. Hair levels of Cr, Cu, I, Mn, Ni, Si and Al in men decreased with age, whereas hair Co, Fe, Se, Cd, Li and Pb content tended to increase. Hair mercury increased in association with age in men and in women, whereas hair vanadium was characterised by a significant decrease in both sexes. The difference in hair trace element content be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
3
16
1
1
Order By: Relevance
“…2). Similar in the study by Skalnaya et al (2016), the content of Hg in hair was increased in men with age. Furthermore, considering all patients (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…2). Similar in the study by Skalnaya et al (2016), the content of Hg in hair was increased in men with age. Furthermore, considering all patients (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Michalak et al (2014) reported an increase in Hg content of hair samples with age (examined age groups: from 0 to 10 years old to >60 years old). Skalnaya et al (2016) obtained significantly higher content of Hg in hair samples in patients over 30 years of age compare to younger patients (age group 10–29 years old). Also, the study by McDowell et al (2004) showed an increase in mercury content in hair with age (examined age groups: from 1 to 5 years old to 16–49 years old).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar results were obtained when comparing the values of the metal concentration between male (median 0.222 mg/kg for 10–19 years old and 0.241 mg/kg for 20–29 years old) and female (median 0.261 mg/kg for 10–19 years old and 0.298 mg/kg for 20–29 years) of the Orenburg Region. Also, in the study in question, it was found that gender differences in the levels of trace elements, including mercury, were less pronounced with age ( Skalnaya et al., 2015 ). The opposite trend was observed when studying the mercury content in the hair of Polish students - in males (mean 0.216 mg/kg), the metal concentration is higher than in females (mean 0.204 mg/kg) ( Chojnacka et al., 2010 ).…”
Section: Discussionmentioning
confidence: 89%
“…[25][26][27][28] However, only limited information is available on the age-and gender-related differences in the elements in the scalp hair of diabetic subjects. 10,15) Furthermore, renal disorders and hypertension, which are most common complications associated with diabetes, affect the levels of elements in the hair of diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%